Crystal structure of N-(adamantan-1-yl)-4-methylpiperazine-1-carbothioamide, C16H27N3S - Al-Wahaibi Lamya H.; Blacque Olivier; Tiekink Edward R. T.; El-Emam Ali A. (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C16H27N3S, monoclinic, P21/c (no. 14), a = 11.54650(10) Å, b = 15.13080(10) Å, c = 9.25160(10) Å, β = 103.137(1)°, V = 1574.03(2) Å3, Z = 4, R gt(F) = 0.0305, wRref (F 2) = 0.0807, T = 160 K.